Toward an Understanding of the Characteristics of Secondary School Cyberhate Perpetrators - Blaya, Catherine; Audrin, Catherine (Frontiers in Education, 2019)
While the Internet offers many opportunities to access information, training and communication, it has created new grounds for risks, threats and harm. With the rise of populism and extremism, new forms of cyberbullying emerge, more specifically cyberhate. The Internet has become a privileged tool to disseminate hatred, based on racism, xenophobia, bigotry and islamophobia. Organized groups use the internet as a dissemination tool for their ideas, to build collective identity and to recruit young people. The presence of these groups has been facilitated worldwide thanks to technology. Yet, little attention has been granted to the way the Internet eases the activities of individuals who promote and propagate hate online. The role they play in spreading racism, xenophobia and bigotry is paramount as they regularly comment online about news and events, interacting with like-minded people with impunity because the web prevents people from being easily identified or controlled. While literature on exposure to hateful contents and cyberhate victimization is growing, little is known about who the perpetrators really are. A survey with young people aged 12-20 (N= 1,889) was completed in France and forms the basis of this article. It provides an understanding of the characteristics and associated variables of cyberhate perpetration. The Structural Equation model shows that cyberhate perpetration is heavily related to time spent online, victimization, belonging to a deviant youth group, positive attitudes towards violence and racism. Results from the SEM further suggest that people who suffered from online victimization will themselves have a greater tendency to belong to deviant youth groups. Multiple mediation analysis further suggests that trust in institutions may however prevent young people from belonging to a deviant youth group and decrease positive attitudes toward violence, thus diminishing the tendency to perform hateful aggression.